The Influence of the Creative Problem-Solving Model Assisted by Fraction Puzzle Media on Problem-Solving Ability in Mathematics Learning: Pengaruh Model Pemecahan Masalah Kreatif Berbantuan Media Teka-teki Pecahan terhadap Kemampuan Pemecahan Masalah dalam Pembelajaran Matematika - Suryaningsih, Tri; Zulfatunnisa, Shobrina (JENIUS :Journal of Education Policy and Elementary Education Issues, 2025)
Problem-solving ability is one of the key competencies of the 21st century in facing complex and dynamic real-life challenges. This study examines the effect of the Creative Problem Solving Model assisted by fraction puzzle media on mathematical problem-solving abilities. This research was conducted at MI Jauharotul Huda in the 2023/2024 Academic Year. The method used was a quasi-experimental study with a posttest-only control Group Design. The sample was taken using the Random Sampling technique, with class VA students as the experimental group and class VB students as the control group. The test given was in the form of 10 essay questions. Based on the results of the t-test calculation using the Independent Sample t-test method on the post-test of both classes, the results obtained p = 0.000, so H₀ was rejected, and H₁ was accepted. The average score for problem-solving abilities in the experimental class was 64.38, while in the control class, it was 49.92. This result shows that the Creative problem-solving model assisted by fraction puzzle media significantly improves students' mathematical problem-solving abilities. Based on the results of this study, teachers can consider implementing the Creative Problem Solving model assisted by concrete media, such as fraction puzzles, as an effective learning model to improve mathematical problem-solving skills.